2020
DOI: 10.1002/mds.28057
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Clinically Important Differences for Burke‐Fahn‐Marsden Dystonia Rating Scale and 36‐Item Short‐Form Health Survey

Abstract: BackgroundAlthough an increasing number of trials are reported on the treatment of generalized or segmental isolated dystonia, the minimal clinically important difference thresholds for the most frequently reported outcome measures are still undetermined.ObjectivesTo estimate the minimal clinically important difference for the Burke‐Fahn‐Marsden Dystonia Rating Scale and the 36‐Item Short‐Form Health Survey in generalized or segmental dystonia.MethodsA total of 898 paired examinations of 198 consecutive patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
0
20
0
1
Order By: Relevance
“…4b ). 68 While the funnel plot suggested possible publication bias for the analysis of all studies, asymmetry was not detected for the analysis of studies reporting on the BFMDRS‐Movement (Fig. S2 , online supporting information).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…4b ). 68 While the funnel plot suggested possible publication bias for the analysis of all studies, asymmetry was not detected for the analysis of studies reporting on the BFMDRS‐Movement (Fig. S2 , online supporting information).…”
Section: Resultsmentioning
confidence: 97%
“…5b ). 68 This finding is limited by serious risk of bias and imprecision. Publication bias was undetected (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Threshold values for the DDS were 0.5 points for improvement. The cutoff score for the global score of the 36-Item Short-Form Health Survey was 6.5 points for clinically meaningful improvement [33]. According to this statement, the vast majority of patients in this series had a meaningful improvement after STN-DBS (Table 2).…”
Section: Discussionmentioning
confidence: 70%
“…Lastly, we observed that the LFO of patients who had been chronically treated with cDBS were considerably lower than those of DBS-naïve patients, even when stimulation was suspended. From all the patients treated with chronic cDBS, most of them (4/5) presented more than the minimal clinically important improvement in dystonic symptoms [11] one year after DBS implantation. Since LFO are correlated with the severity of dystonic symptoms [4], it is possible that the LFO-suppression that takes place during cDBS occurs in a gradual manner, parallel to the gradual reduction in dystonic symptoms observed after cDBS is switched on.…”
Section: Discussionmentioning
confidence: 99%